A Balancing Act: How Organizations Pursue Consistency in Routine Functioning in the Face of Ongoing Change - Turner, Scott F.; Rindova, Violina (Organization Science, 2012)
This study examines how participants in routines view and balance pressures for consistency in the face of ongoing change. We address this question through a qualitative case-based inquiry into the ostensive aspects of the core operational routine in six waste management organizations. We find that organizational members simultaneously establish and maintain two ostensive patterns—one of targeted consistency and another of flexibility in internal coordination—by leveraging artifacts and connections. Organizations, however, could not establish similar patterns among their customers, who, lacking connections with other routine participants, expected consistency and performed their part less flexibly. These observations lead us to develop a theoretical model that identifies the processes through which simultaneous ostensive patterns of consistency and flexibility are established and sustained among organizational members, as well as the challenges that arise from multiplicity of ostensive patterns among routine participants with different roles and connections. The model advances the dynamic perspective on routines by articulating how artifacts and connections support the balancing of pressures for consistency and for change in routine functioning.